Classifying Adults with Binge Eating Disorder Based on Severity Levels. (20th April 2017) - Dakanalis, Antonios; Riva, Giuseppe; Serino, Silvia; Colmegna, Fabrizia; Clerici, Massimo
Abstract: The clinical utility of the severity criterion for binge eating disorder (BED), introduced in the DSM‐5 as a means of addressing heterogeneity and variability in the severity of this disorder, was evaluated in 189 treatment‐seeking adults with (DSM‐5) BED. Participants classified with mild, moderate, severe and extreme severity of BED, based on their weekly frequency of binge eating episodes, differed significantly from each other in body mass index (BMI), eating disorder features, putative factors involved in the maintenance process of the disorder, comorbid mood, anxiety and personality disorders, psychological distress, social maladjustment and illness‐specific functional impairment (medium‐to‐large effect sizes). They were also statistically distinguishable in metabolic syndrome prevalence, even after adjusting for BMI (large effect size), suggesting the possibility of non‐BMI‐mediated mechanisms. The implications of the findings, providing support for the utility of the binge frequency as a severity criterion for BED, and directions for future research are outlined. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association